Elevated serum complement C3 levels are associated with prehypertension in an adult population. (2nd January 2017) - Bao, Xue; Meng, Ge; Zhang, Qing; Liu, Li; Wu, Hongmei; Du, Huanmin; Shi, Hongbin; Xia, Yang; Guo, Xiaoyan; Liu, Xing; Han, Peipei; Dong, Renwei; et al.
ABSTRACT: Prehypertension is a public health epidemic associated with various adverse outcomes, but can be reversed by timely intervention. However, little attention has been paid to prehypertension. Complement C3 is a central hub of complement-related immune system. We examined the association between C3 and prehypertension in an adult population for the first time, aiming to investigate whether pro-inflammatory immune response is involved in the prehypertensive state. About 7820 Tianjin residents without hypertension were categorized into sex-specific quintiles based on their serum concentration of complement C3. Adjusted logistic regression models were used separately by gender to assess the association between C3 quintiles and the prevalence of prehypertension. After multiple adjustment, the odds ratios (95% confidence interval) for prehypertension across increasing quintiles of C3 were 1.00 (reference), 1.02 (0.84, 1.25), 1.15 (0.94, 1.42), 1.25 (1.01, 1.54), and 1.71 (1.35, 2.17) ( p for trend < 0.0001) among men and were 1.00 (reference), 1.17 (0.92, 1.49), 1.13 (0.88, 1.44), 1.15 (0.89, 1.48), and 1.40 (1.07, 1.84) ( p for trend = 0.03) among women. The findings suggested that elevated serum C3 levels are associated with prehypertension. Reducing inflammation may be a potential therapeutic strategy for prehypertension and hypertension that is worthy of further studies and discussion.